Wave-induced sediment dynamics and seabed changes around the Truong Sa Island, Vietnam - Nguyen Xuan, Tung; Nguyen Minh, Huan; Nguyen Kim, Cuong; Pham Duc, Hung; Luc Anh, Tuan (Vietnam Journal of Earth Sciences, 2025)
This study investigated wave-induced suspended sediment dynamics and seabed morphological changes around the Truong Sa Island in the East Vietnam Sea. The analysis was conducted using the MIKE 21/3 Coupled Model FM, which integrates wave, hydrodynamic, sediment transport, and bed evolution modules to simulate seabed responses to both seasonal and interannual wave forcing during 2013–2015. The model was forced with ERA5 reanalysis data and validated using observed tidal and bathymetric datasets from the Vietnam Academy of Science and Technology (VAST). Results revealed that seabed changes were most pronounced in the northeastern nearshore region of the Truong Sa Island. It was driven by the prevailing northeast-directed wave conditions, which also contributed to elevated suspended sediment concentrations (SSCs). Seasonally, winter exhibited more dynamic seabed changes and greater suspended sediment variability than summer. Under the most severe wave conditions in 2015, the simulated domain experienced a net seabed incision with an average depth of -0.54 m. Spatially, the nearshore areas were characterized by significant seabed incision and high SSCs, whereas offshore regions showed minimal seabed changes and low SSCs. Moreover, persistent sediment deposition was observed in the harbor southwest of the Truong Sa Island, implying the need for regular dredging to maintain operational capacity. The findings underscore the need for integrated management strategies that balance coastal development, marine ecosystem protection, and navigational safety.